2002
DOI: 10.1002/cne.10178
|View full text |Cite
|
Sign up to set email alerts
|

Hypophysiotropic neurons of the paraventricular nucleus respond in spatially, temporally, and phenotypically differentiated manners to acute vs. repeated restraint stress: Rapid publication

Abstract: Hypothalamic-pituitary-adrenal (HPA) responses to stress are initiated by parvicellular neurosecretory neurons in the medial parvicellular (mp) part of the paraventricular hypothalamic nucleus (PVH), which express corticotropin-releasing factor (CRF), among other neuropeptides. We have used an approach guided by patterns of stress-induced Fos expression to explore the manner in which anatomically and phenotypically defined components of the mpPVH respond to acute vs. repeated restraint stress. Hormonal indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
95
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 58 publications
15
95
1
1
Order By: Relevance
“…The suppression of corticosterone secretion following exposure to stress was accompanied by a reduction in neuronal activation of the mpdPVN of the hypothalamus, an area that contains all the CRH neurosecretory cells that regulate ACTH secretion through communication with the anterior pituitary. Although we did not assess CRH mRNA in this study, the region of interest we analyzed in the mpdPVN here is where all CRH neurosecretory cells are amassed (Viau and Sawchenko, 2002;Viau et al, 2005) suggesting that a suppression of stress-induced activation of CRH neurosecretory cells is likely mediating the effect of desipramine in this study. In support of this hypothesis, a recent report has demonstrated that reductions in stress-induced CRH transcription are associated with suppression of stressinduced peripheral corticosterone secretion following desipramine treatment (Conti et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The suppression of corticosterone secretion following exposure to stress was accompanied by a reduction in neuronal activation of the mpdPVN of the hypothalamus, an area that contains all the CRH neurosecretory cells that regulate ACTH secretion through communication with the anterior pituitary. Although we did not assess CRH mRNA in this study, the region of interest we analyzed in the mpdPVN here is where all CRH neurosecretory cells are amassed (Viau and Sawchenko, 2002;Viau et al, 2005) suggesting that a suppression of stress-induced activation of CRH neurosecretory cells is likely mediating the effect of desipramine in this study. In support of this hypothesis, a recent report has demonstrated that reductions in stress-induced CRH transcription are associated with suppression of stressinduced peripheral corticosterone secretion following desipramine treatment (Conti et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Discrete localization of Fos-ir profiles to the dorsal medial parvocellular (neuroendocrine anterior pituitary regulating) population of the PVN (mpdPVN) was accomplished by limiting the region of interest to the area medial to the magnocellular population, lateral to the periventricular zone, and ventral to the dorsal cap, as has been carried out previously. This conservative analysis ensures that all slices are examined at the same rostral-caudal axis and also ensures that the region of interest is where all the CRH neurosecretory cells, which communicate to the anterior pituitary to stimulate ACTH, are amassed (Viau et al, 2005;Viau and Sawchenko, 2002). Cell number estimates were generated by counting bilaterally the number of Fospositive cells through the medial parvocellular cell population, averaged by dividing cell counts by slice number, and corrected for sampling frequency (one in five sections, 150-mm intervals) by multiplying this product by a factor of five.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…In particular, chronic stress can lead to potentiated basal ACTH and/or corticosterone secretion, adrenal hypertrophy and elevated PVN CRH and AVP mRNA and protein expression (Hauger et al, 1988;Herman et al, 1995;Kiss and Aguilera, 1993;Ulrich-Lai et al, 2006b). Chronic exposure to homotypic stressors typically engender some degree of HPA axis habituation (Dhabhar et al, 1997;Odio and Brodish, 1989;Pitman et al, 1988;Viau and Sawchenko, 2002). However, despite the presence of an enhanced glucocorticoid feedback signals, HPA responses to new stressors are either maintained or augmented following chronic stress a process known as stress facilitation (Armario et al, 1985;Bhatnagar and Dallman, 1998;Bhatnagar and Vining, 2003;Dallman et al, 1992;Hauger et al, 1990;Kiss and Aguilera, 1993;Ostrander et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Rats in repeated stress groups were exposed to 8 consecutive days of 30 min restraint per day. We, and other groups, have observed habituation of ACTH and corticosterone responses following 30min of restraint per day for 8 days and up to14 days (Viau and Sawchenko, 2002;Jaferi et al, 2003;Jaferi & Bhatnagar, 2006).…”
Section: Repeated Stress Paradigmmentioning
confidence: 60%
“…Together, the evidence discussed above suggests that activity in the mPFC regulates both acute and repeated stress-induced HPA activity. Repeated exposure to the same, homotypic stressor can produce a gradual decrement, or habituation, of HPA activity (Bhatnagar & Meaney, 1995;Li & Sawchenko, 1998;Garcia et al, 2000;Viau and Sawchenko, 2002;Jaferi & Bhatnagar, 2006). Habituation to repeated stress may involve discrimination of the stressor as a familiar and previously encountered stressor as opposed to one that is novel.…”
Section: Introductionmentioning
confidence: 99%